Respon Pertumbuhan dan Hasil Tanaman Jagung (Zea Mays L.)Terhadap Pemberian Pupuk Majemuk P dan K - Eso Solihin; Rija Sudirja; Haris Maulana; Nadia Nuraniya Kamaluddin (Jurnal Pertanian Khairun, 2023)
The use of phosphorus and potassium compound fertilizers has become a commonly used strategy in modern agricultural practices to increase crop yields, optimize land use, and minimize environmental impacts. This study aims to determine the effect of applying a combination of PK (53–34) compound fertilizer doses on increasing the growth and yield of maize (Zea mays L.). This research was conducted at the Experimental Garden of the Faculty of Agriculture, Jatinangor Campus, Sumedang Regency, West Java. The altitude of the place is about 750 meters above sea level. The method in this study used a randomized group design (RAK) with ten treatments and three replications. Treatment A (Control), (B) Standard fertilizer (Urea, SP-36, and KCl), (C) 1 Urea + 1/2 PK, (D) 1 Urea + 1 PK, (E) 1 Urea + 1 ½ PK, (F) 3/4 Urea + ½ PK, (G) 3/4 Urea + 1 PK, (H) 3/4 + 1 ½ PK, (I) ½ Urea + 1 PK, and (J) 1 PK. The results showed that the doses of urea fertilizer (225 kg ha-1) and PK compound (60 kg ha-1) gave the best results on plant height, number of leaves, cob length, cob diameter, cob weight with cob, cob weight without cob, and weight per hectare.